2014
DOI: 10.5194/acp-14-8781-2014
|View full text |Cite
|
Sign up to set email alerts
|

EARLINET dust observations vs. BSC-DREAM8b modeled profiles: 12-year-long systematic comparison at Potenza, Italy

Abstract: Abstract. In this paper, we report the first systematic comparison of 12-year modeled dust extinction profiles vs. Raman lidar measurements. We use the BSC-DREAM8b model, one of the most widely used dust regional models in the Mediterranean, and Potenza EARLINET lidar profiles for Saharan dust cases, the largest one-site database of dust extinction profiles. A total of 310 dust cases were compared for the May 2000-July 2012 period. The model reconstructs the measured layers well: profiles are correlated within… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
76
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(85 citation statements)
references
References 68 publications
8
76
0
1
Order By: Relevance
“…The relatively low local aerosol content makes the observations particularly interesting for long-transported particle plumes Mona et al, 2014). In Fig.…”
Section: Potenzamentioning
confidence: 99%
“…The relatively low local aerosol content makes the observations particularly interesting for long-transported particle plumes Mona et al, 2014). In Fig.…”
Section: Potenzamentioning
confidence: 99%
“…In the next step, dual-wavelength Raman lidar came into operation (Müller et al, 1998;Ansmann et al, 2000;Mattis et al, 2002;Wandinger et al, 2002;Murayama et al, 2004) with laser wavelengths at 355 and 532 nm and respective vibrational-rotational nitrogen Raman channels at 387 and 607 nm. The aerosol Raman lidar technique opened a solid way for comprehensive studies of anthropogenic pollution, desert dust, volcanic dust, and biomass burning smoke at several wavelengths (e.g., Mattis et al, 2004;Müller et al, 2005;Tesche et al, 2009a;AladosArboledas et al, 2011;Groß et al, 2011Groß et al, , 2012Nicolae et al, 2013;Kanitz et al, 2014;Veselovskii et al, 2016) and found broad application in the European Aerosol Research Lidar Network, EARLINET (e.g., Amiridis et al, 2005;Papayannis et al, 2008;Mona et al, 2014;Pappalardo et al, 2014). Particle extinction profiling is also a basic requirement for a successful retrieval of microphysical aerosol properties by means of inversion methods (Müller et al, 1998;Müller et al, 2000;Müller et al, 2013;Ansmann and Müller, 2005;Veselovskii et al, 2002Veselovskii et al, , 2016.…”
Section: Introductionmentioning
confidence: 99%
“…In the height range 2.7-5 km, the agreement is satisfactory with an EARLINET mean value of Saer=50.4±5.2 sr, suggesting that all the aerosol types identified compensate for this situation or the aerosol fields over the grid are frequently dust affected. The latter stems from EARLINET based studies, such as the study of [8] where the authors used a multiyear dust database and found values lidar ratio of ~50 sr for the site of Potenza. Figure 3 reports the classification of aerosol features of the CALIPSO overpasses and the corresponding Potenza station observations.…”
Section: Resultsmentioning
confidence: 99%